Effects of lifting heights on lifting performances - Luo, Jiantong. (2012)
Manual lifting is the act of moving a load vertically with both hands without any mechanical assistance. Musculoskeletal disorders, especially lower back pain, usually occur due to inappropriate lifting. Therefore, many studies were carried out to research on appropriate lifting strategies and task design to reduce the risk of lower back injuries. However, previous studies had failed to establish a relationship between strength and exertion height, while the effects of genders were also rarely discussed. Therefore, this study aimed to determine the effects of exertion heights on lifting performance, which were determined from position-time data, and whether a relationship exist between gender and lifting performances. Motion data was collected from 12 healthy and inexperienced subjects using motion capturing devices and was further processed to obtain the lifting performance parameters. Results revealed a possible relationship between lifting performances and lifting heights, most noticeably the trunk angular ROM increasing with exertion heights. A higher exertion height is more likely to cause lower back pain as trunk angular ROM is associated to the stress experienced at the lower back. In addition, possible interaction between gender and several lifting performance indicators was also observed, with females having higher trunk angular ROM, mean angular velocity and mean angular acceleration than males. Finally, this study concluded by providing recommendations for future studies